2014
DOI: 10.1177/0969141314561707
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer screening with HPV testing in the Valcamonica (Italy) screening programme

Abstract: HPV-based screening increases colposcopies at the first round, but also strongly increases the detection rate. At the second round, HPV prevalence was much lower and the detection rate also fell, corroborating the need for longer screening intervals in HPV-negative women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 27 publications
(51 reference statements)
10
17
0
Order By: Relevance
“…As HPV positivity rates are strictly associated with the age of the target population, the local circulation of high‐risk HPV types (greatly variable across different countries), and the screening interval, our results cannot be directly compared with other data from the literature. Nonetheless, our figures are in line with another Italian pilot programme with the same age range and screening interval (8.7% at first screening; 3.9% at the second screening) . Moreover, the Pobascam trial also reported a reduction by about one‐quarter (from 4.5 to 3.3%) of HPV positivity at the second screening with a 5‐year interval …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As HPV positivity rates are strictly associated with the age of the target population, the local circulation of high‐risk HPV types (greatly variable across different countries), and the screening interval, our results cannot be directly compared with other data from the literature. Nonetheless, our figures are in line with another Italian pilot programme with the same age range and screening interval (8.7% at first screening; 3.9% at the second screening) . Moreover, the Pobascam trial also reported a reduction by about one‐quarter (from 4.5 to 3.3%) of HPV positivity at the second screening with a 5‐year interval …”
Section: Discussionsupporting
confidence: 90%
“…Moving from the first to the second screening, the colposcopy workload was more than halved (2.0 versus 4.4%). Thus, even if the workload generated by the HPV‐based protocol exceeds that of cytology‐based screening, this seems to be limited to the first round. This result needs to be confirmed for a 5‐year interval.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported by other Italian HPV-based screening pilot projects, we observed a higher participation in the programme compared with the historical participation rate in the Pap test screening program (Confortini et al , 2010; Zorzi et al , 2013b; Pasquale et al , 2015). The new test could be more appealing, making the public screening programme more competitive than the opportunistic screening in the private sector, which did not have the possibility to offer the HPV test at reasonable prices during the study period.…”
Section: Discussionsupporting
confidence: 77%
“…Longitudinal data from RCTs on persistently HPV16-positive women with no lesions detected should also be evaluated to define their longterm risk and best follow-up strategy before implementation of triage by partial genotyping. Finally, in the screening context, two additional caveats must be kept into consideration in the near future; namely, the different risk of precursor lesions in the first versus the subsequent hrHPV-based rounds, much lower in the second (16), and the screening strategy for vaccinated women, in whom lesions caused by types 16 and 18 will gradually disappear, and specific protocols will have to be designed.…”
mentioning
confidence: 99%